2020
DOI: 10.1186/s40170-020-00212-x
|View full text |Cite
|
Sign up to set email alerts
|

PHGDH supports liver ceramide synthesis and sustains lipid homeostasis

Abstract: Background: D-3-phosphoglycerate dehydrogenase (PHGDH), which encodes the first enzyme in serine biosynthesis, is overexpressed in human cancers and has been proposed as a drug target. However, whether PHGDH is critical for the proliferation or homeostasis of tissues following the postnatal period is unknown. Methods: To study PHGDH inhibition in adult animals, we developed a knock-in mouse model harboring a PHGDH shRNA under the control of a doxycycline-inducible promoter. With this model, PHGDH depletion can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
3
14
0
1
Order By: Relevance
“…Despite evident regulation of the serine synthesis genes PHGDH, PSAT1, and PSPH by insulin signaling through mTORC1 and ATF4 in primary hepatocytes, we failed to detect any regulated flux through the serine synthesis pathway, which was extremely low under all conditions tested. Our findings are consistent with data from a recent study that showed the fractional enrichment of serine (m+3) synthesized from 13 C 6 -glucose in the liver was minimal (<1%) [ 71 ]. Thus, despite clear regulation of the serine synthesis enzymes, hepatocytes might rely predominantly on exogenous serine.…”
Section: Discussionsupporting
confidence: 93%
“…Despite evident regulation of the serine synthesis genes PHGDH, PSAT1, and PSPH by insulin signaling through mTORC1 and ATF4 in primary hepatocytes, we failed to detect any regulated flux through the serine synthesis pathway, which was extremely low under all conditions tested. Our findings are consistent with data from a recent study that showed the fractional enrichment of serine (m+3) synthesized from 13 C 6 -glucose in the liver was minimal (<1%) [ 71 ]. Thus, despite clear regulation of the serine synthesis enzymes, hepatocytes might rely predominantly on exogenous serine.…”
Section: Discussionsupporting
confidence: 93%
“…Despite evident regulation of the serine synthesis genes PHGDH, PSAT1, and PSPH by insulin signaling through mTORC1 and ATF4 in primary hepatocytes, we failed to detect any regulated flux through the serine synthesis pathway, which was extremely low under all conditions tested. Our findings are consistent with data from a recent study that showed the fractional enrichment of serine (m+3) synthesized from 13 C6-glucose in the liver was minimal (<1%) [64]. Thus, despite clear regulation of the serine synthesis enzymes, hepatocytes might rely predominantly on exogenous serine.…”
Section: Discussionsupporting
confidence: 92%
“…These observations show some parallels to other approaches aimed at limiting the supply of NEAAs to cancers that are already in clinical use, such as treatment of patients with ASS1 deficient cancers (so blocking the de novo pathway of arginine synthesis) with ADI-PEG20, to degrade circulating arginine 41 . Consistent with a recent study showing no overt toxicity associated with depletion of PHGDH in adult mice (sparing the brain) 42 , mice fed on a normal diet tolerated treatment with PH755 well, showing that in the presence of exogenous serine, inhibition of the SSP was not detrimental to health. Similarly, PH755 did not affect the growth of cells in serine and glycine containing medium.…”
Section: Discussionsupporting
confidence: 89%